Efficacy and Safety of the Fixed-Dose Combination of Atorvastatin/Fenofibrate Versus Atorvastatin on the Lipid Profile of Patients with Type 2 Diabetes and Dyslipidemia - Padilla-Padilla, Francisco G.; Ruiz-Bernes, Lina N.; Román-Pintos, Luis M.; Peraza-Zaldívar, Juan A.; Sander-Padilla, José G.; Lugo-Sánchez, Laura A.; Rios-Brito, Kevin F.; Arguedas-Núñez, María M.; Flores-Huanosta, Diana; González-Canudas, Jorge (Cardiology and Therapy, 2025)
Introduction In dyslipidemia associated with type 2 diabetes (T2DM), elevated triglycerides (TG), increased low-density lipoprotein cholesterol (LDL-C), and decreased high-density lipoprotein cholesterol (HDL-C) levels are commonly found, resulting in a high prevalence of mixed dyslipidemia among patients with T2DM. Therefore, the combination therapy of atorvastatin/fenofibrate may be useful for simplifying pharmacological regimens, enhancing adherence, and requiring fewer doses of each drug to achieve the target, which decreases the number of adverse events. Methods We conducted a randomized multicenter, double-blind clinical trial of patients with T2DM and mixed dyslipidemia to evaluate the magnitude of change in lipid profile with a fixed-dose combination (FDC) therapy group of atorvastatin 20 mg/fenofibrate 160 mg (G_FDC) versus atorvastatin 20 mg monotherapy group (G_M), both oral route, one tablet every 24 h. The magnitude of change in the lipid profile at 2 and 4 months was compared within each group and between groups using the analysis of variance (ANOVA) test. A p value ≤ 0.05 was considered statistically significant. Results A total of 76 patients were included (38 per group), with an age of 56.7 ± 10.2 years, and 56.6% were women. The values at 4 months for G_FDC vs. G_M were as follow: TG mg/dL (−144.3 vs. −64.0, p = 0.004), TG percentage change (%C) (−47.9 vs. −33.1, p = 0.007); LDL-C mg/dL (−50.5 vs. −51.7, p = 0.784), LDL-C %C (−42.5 vs. −45.6, p = 0.899). The percentage of patients who achieved the targets for triglycerides (TG) was 56.7% compared to 43.8% ( p = 0.309), while for LDL-C, it was 73.3% compared to 78.1% ( p = 0.660). Finally, the predictive cardiovascular risk indices (∆ of change) showed a TG/HDL index of −3.9 ± 4.6 vs. −1.5 ± 2.9 ( p = 0.015) and a Tg/glucose index of −0.7 ± 0.5 vs. −0.3 ± 0.4 ( p = 0.003). Conclusion The FDC therapy of atorvastatin 20 mg/fenofibrate 160 mg achieved a greater percentage reduction in lipid profile than atorvastatin alone. No differences in adverse events were observed between the groups. Clinical Trials Registration ClinicalTrials.gov No. NCT04882293, registration date: February 28, 2022.